Pengaruh Kualitas Layanan Akademik Terhadap Citra Lembaga Di Sekolah Tinggi Ilmu Ekonomi Dahani Dahanai Buntok: The Effect Of Academic Service Quality On Institutional Image In High School Of Economic Science Of Buntok - Kurniaty, Harlina (Pencerah Publik, 2017)
This study is aimed at finding out whether there is an influence between academic services and the image of the Institute in the College of Economics Dahani Dahanai Buntok partially and simultaneously and which variables most influence the image of the institution For this study the authors used a theory according to Parasuraman, Zeithmal, and Berry (1988) about the five dimensions of service namely aspects of direct evidence, aspects of reliability, aspects of responsiveness, aspects of assurance and aspects of empathy. For the measurement of the research instrument the author uses a Likert scale, while for the analysis of the data this study uses a validity and reliability test, a classic assumption test, a multiple linear regression test, a t test and an F test, using SPSS version 17.0. The results of this study indicate that based on a simple linear regression test the value obtained for the Image (Y) is 9,688, variables X1,0,026, X20,017, X3-0,101, X40,351, X50,118, it can be seen that for the value of X1 ¬ X2X4 and the positive coefficient X5 means that there is a good influence between the variable with the image of the institution, while the negative coefficient X3 variable means that the X3 variable value decreases the institution’s image will decrease in the eyes of students. So it can be seen that the most influential variable increasing the image of the institution is the Assurance (X4) variable and the variable that must be immediately addressed by the management of the STIE DD is the Responsiveness variable (X3) because if it is not immediately responded it will further reduce the institution’s image.